Frequency of rhabdiasid nematodes in wild Crotalus durissus terrificus (Serpentes, Viperidae) from Botucatu region, São Paulo State, Brazil - Da Silva, Reinaldo José [UNESP]; Nogueira, M. F. [UNESP]; Barrella, T. H. [UNESP]; Takahira, R. K. [UNESP] (FapUNIFESP (SciELO), 2007)
The aim of the present study was to evaluate the frequency of rhabdiasid nematodes in recently captured Crotalus durissus terrificus snakes from São Paulo State, Brazil. Fifty snakes (34 males and 16 females) were studied and each one was evaluated for the presence of that nematode at the moment of receipt at the Institution and after 90 days of quarantine inside individual cages. Tracheopulmonary washes were examined. Snakes that died during quarantine underwent necropsy and lung examination. Analysis of the results obtained at the two evaluation times (0 and 90 days), in addition to the data obtained during necropsies, showed that 44% (18 males and 4 females) of the C. d. terrificus snakes were naturally infected by rhabdiasid nematodes. These data demonstrate the parasitism level in natural conditions and are important for the sanitary handling of these reptiles in captivity.
Keywords: Crotalus durissus terrificus; Frequency; Nematoda; Rhabdias; Snakes; Viperidae; Reptilia; Rhabdiasida; Serpentes